Problems of code of products that affect the inventory management: cuban companies case study (2014)
Numerous code systems and classification of products and services exist globally, being tendency the standardization of them in the supply chains to achieve higher integration. The correct use of these systems is considered essential in the effectiveness in the inventory management, given its direct relationship with the registration of the primary information and tracing of the products. However, the scientific literature and the academic programs concentrate mostly on the Auto-ID technologies more than in the code structure and the consequences of an incorrect use of the code. The present article reflects the main deficiencies possible to detect in the systems of code of products, using a sample of companies in Cuba. The consequences of these deficiencies are discussed and it is also included a proposal of organization of the code for the Cuban companies.